Syntheses, crystal structures and luminescent properties of Ag(I) complexes with benzilic carboxylate and 2, 6-pyridinedicarboxylate. Issue 8 (3rd August 2017) - Fu, Wei-Wei; Xu, Liu; Zhang, Yan-Hua; Chen, Man-Sheng
ABSTRACT: Two complexes [Ag(bpy)(H2 O)]·(Hbac) (1 ) and [Ag2 (bpy)2 (H2 O)2 ](pdc)·(H2 O)5 (2 ) (H2 bac = benzilic acid, bpy = 4, 4′-bypyridine, H2 pdc = 2, 6-pyridinedicarboxylic acid) have been synthesized and characterized by IR, element analysis, X-ray-single crystal diffraction and TGA. Crystal data for1 : Monoclinic, space group C2/c, a = 18.8192(5) Å, b = 12.7131(5) Å, c = 17.8373(8) Å, β = 95.745(4)°, V = 4246.1(3) Å 3 and Z = 8;2 : Triclinic, space group, P-1, a = 8.132(5) Å, b = 10.485(6) Å, c = 18.026(10) Å, α = 96.194(10)°, β = 91.047(11)°, γ = 105.866(10)°, V = 1468.0(15) Å 3 and Z = 2. In complex1, Ag(I) is coordinated by two discrete 4, 4′-bpy ligands and one water molecule and Hbac − behaves as a counterpart anion. In the crystal, a 3D network was formed by hydrogen bonds and π–π face-to-face interactions. In complex2, Ag(I) is also coordinated by two discrete 4, 4′-bpy ligands and one water molecule and pdc 2− behaves as a counterpart anion, too. In the crystal, a similar 3D network was formed by hydrogen bonds and π–π face-to-face interactions as well as that of complex 1. The luminescence properties of 1 and 2 have been investigated.